Effect of pilates on the physical and mental health of drug-dependent individuals — a randomized controlled trial - Feng Ji; Ensong Zhou; Peng Zhao; Xinliang Chen; Hui Wang; Jiabin Zhong; Yi Zhang; Yunhang Lu; Qing Zhang (BMC Psychiatry)
Abstract Objective Drug-dependent individuals often face severe physical and mental health impairments, necessitating safe and adaptable rehabilitation strategies. This study aims to investigate the effects of Pilates exercise on the physical and mental health of drug-dependent individuals. Specifically, the study seeks to evaluate changes in body composition, physical fitness, blood biochemistry, and psychological outcomes following a structured Pilates intervention. Methods This study was conducted as a double-blind, parallel-group, randomized controlled trial. A total of 43 substance-dependent individuals were recruited from the Judong Drug Rehabilitation Center and randomly assigned to either the Pilates intervention group (n = 22) or the control group (n = 21). The experimental group underwent Pilates program of two weekly sessions for 24 weeks, while the control group received conventional rehabilitation. We assessed physical and mental health indicators at baseline, 12, and 24 weeks. Repeated measures analysis of variance was employed to discern inter-group differences, and Spearman correlation analysis was applied to assess the relationship between fluctuations in scores on anxiety and depression scales and those of associated physiological metrics. Results After 24 weeks of Pilates intervention, the intervention group showed significant improvements (p < 0.05) in body fat percentage, skeletal muscle mass, sit-and-reach distance, push-up performance, one-leg standing with eyes closed, vital capacity, white blood cell count, and neutrophil count. Psychological assessments revealed significant differences in scores on the Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS) between the experimental and control groups (p < 0.01), with more pronounced effects in the experimental group. Additionally, changes in SDS scores were correlated with changes in sit-and-reach distance (r = -0.657, p < 0.001), one-leg standing with eyes closed (r = -0.734, p < 0.001), and vital capacity (r = -0.490, p = 0.001). Changes in SAS scores were correlated with changes in the neutrophil-to-lymphocyte ratio (r = -0.304, p = 0.048), platelet-to-lymphocyte ratio (r = -0.320, p = 0.037), sit-and-reach distance (r = -0.595, p < 0.001), one-leg standing with eyes closed (r = -0.704, p < 0.001), and vital capacity (r = -0.472, p = 0.001). Conclusion The Pilates intervention significantly enhanced participants’ physical attributes—body composition, strength, endurance, flexibility, balance, lung function, and immune response—while alleviating anxiety and depression. Correlations were identified between mental health improvements and physical gains, indicating that tailored exercise, informed by ongoing health monitoring, could optimize drug rehabilitation outcomes. Clinical trial registration ChiCTR-IPR-2400087067, Registered on: 18/7/2024.